Breit interaction in dielectronic recombination of hydrogenlike uranium - Bernhardt, Dietrich; Brandau, C.; Harman, Zoltán; Kozhuharov, C.; Müller, A.; Scheid, W.; Schippers, S.; Schmidt, E. W.; Yu, D.; Artemyev, Anton; Tupitsyn, I. I.; Böhm, S.; et al. (Physical review. A, Atomic, molecular, and optical physics, 2011)
Absolute rate coefficients for dielectronic recombination (DR) of H-like U91+ ions have been measured. The electron-ion merged-beam technique at a heavy-ion storage ring was employed using a stochastically cooled ion beam. Thereby, the previously accessible electron-ion collision energies could be greatly extended to the range 63-90 keV. High-resolution DR spectra were measured covering all KLL and KLM resonances. For the resonance strengths, excellent agreement between relativistic theory and experiment is found only if the Breit contribution to the electron-electron interaction is included in the calculations. For the KL1/2L1/2 and KL1/2M1/2 groups the Breit contribution amounts to 44% of their total resonance strengths.